2019
DOI: 10.3389/fphar.2019.00789
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Increases VEGF Expression via CNPY2-PERK Pathway Induced by Hypoxia/Reoxygenation Injury

Abstract: Liraglutide (Lir) is a glucagon-like peptide-1 receptor agonist that lowers blood sugar and reduces myocardial infarct size by improving endothelial cell function. However, its mechanism has not yet been clarified. Unfolded protein response (UPR) plays an important role in the pathogenesis of myocardial ischemia-reperfusion injury. It determines the survival of cells. Endoplasmic reticulum position protein homologue 2 (CNPY2) is a novel initiator of UPR that also participates in angiogenesis. To this extent, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 68 publications
(89 reference statements)
0
7
0
1
Order By: Relevance
“…GLP-1 is an intestinal insulin-stimulating peptide that has several functions, such as lowering blood sugar and improving insulin resistance [ 35 ]. In recent years, liraglutide has received increasing attention for its angiogenic activity in addition to its traditional function of lowering blood glucose levels [ 36 38 ]. Liraglutide promotes angiogenesis to improve heart function [ 37 ], significantly increases hypoxia-inducible factor 1 α (HIF1 α ) and VEGF expression during human umbilical vein endothelial cell (HUVEC) stimulation, and promotes angiogenesis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP-1 is an intestinal insulin-stimulating peptide that has several functions, such as lowering blood sugar and improving insulin resistance [ 35 ]. In recent years, liraglutide has received increasing attention for its angiogenic activity in addition to its traditional function of lowering blood glucose levels [ 36 38 ]. Liraglutide promotes angiogenesis to improve heart function [ 37 ], significantly increases hypoxia-inducible factor 1 α (HIF1 α ) and VEGF expression during human umbilical vein endothelial cell (HUVEC) stimulation, and promotes angiogenesis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, liraglutide has received increasing attention for its angiogenic activity in addition to its traditional function of lowering blood glucose levels [ 36 38 ]. Liraglutide promotes angiogenesis to improve heart function [ 37 ], significantly increases hypoxia-inducible factor 1 α (HIF1 α ) and VEGF expression during human umbilical vein endothelial cell (HUVEC) stimulation, and promotes angiogenesis [ 38 ]. Previous studies have shown that promoting angiogenesis is essential for the survival of flaps [ 5 , 8 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that dapagliflozin increases the expression levels of angiogenic factors in skeletal muscle cells, such as VEGF-A, HGF, FGF2, PDGF-BB, and ANG-1. VEGF-A is the primary angiogenesis inducer, which is required to initiate neovessel formation by promoting endothelial cells' proliferation and migration (Semenza, 2003;Liu et al, 2019), while HGF is a potent mitogen of endothelial cells which works synergistically with VEGF-A to promote endothelial cells' function (Gerritsen, 2005). Furthermore, while VEGF-A is crucial for tube-formation, blood vessels induced merely by VEGF-A are immature and leaky, as they are not covered by the smooth muscle cells (Jain, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in PERK phosphorylation was observed. Although PERK is often associated with increased apoptosis and CHOP induction in heart cells (Prola et al, ; Sun et al, ; Wang, Jia, Zhang, & Wang, ), noncanonical signaling may result in the secondary upregulation of protective factors, such as VEGF (Liu et al, ) In addition, ATF6 induction was abrogated after thapsigargin treatment, suggesting that calreticulin plays a role in the stimulation of this pathway during ER stress. ATF6 activation has been reported to mediate ER stress‐induced injury in several models, indicating that this may be a likely candidate for linking calreticulin to apoptosis (Correll et al, ; Sun et al, ; Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%